Le financement de la formation post-secondaire - Farine, Avigdor; Proulx, Pierre-Paul; Lemelin, Clement (Canadian Journal of Higher Education, 1977)
Higher education occupies a dominant place in the public sector. This paper deals with the direct and indirect costs of post-secondary training, forgone earnings and direct expenditures of students, and student aid programs. It is evident that society at large covers most of the direct costs through the different Government levels, and students the indirect ones (forgone earnings). Government intervention is related to education as investment, the allocation of resources, methods of financing, and student aid programs. Considering the forgone earnings, the resource contribution by students is very important. However, being the main beneficiaries of postsecondary training, it is reasonable to say that those who benefit by that training by receiving higher incomes, should bear a higher percent-age of the institutional costs. To that purpose, a contingent repayment student assistance program seems appropriate. In other respects, in order to interest students in fields of study having social and econ-omic priorities, more scholarships should be made available in them.